Integrating Islamic Ruling And The Medical Concept: A Study Of The Hermaphrodite Inheritance - Raouane Azziz; Ruhi Fadzlyana Jailani; Mualimin Mochammad Sahid (Universiti Sultan Azlan Shah (USAS), Perak, MALAYSIA, 2024)
Indexed by SCOPUS/MYCITE